BEM modeling and experiment verification for thermoacoustic response of suspended nano thin films. (1st September 2021) - Zhou, Zhenhuan; Li, Houyang; Wang, Jinxin; Rong, Dalun; Xu, Xinsheng; Lim, C.W.
Highlights: A novel numerical approach for thermoacoustic response of suspended nano thin films is established. Characteristics of excited acoustic fields in both near and far fields are solved. Accuracy and applicability of two existing analytical models are presented. Influence of irregular deformation of CNT thin films on acoustic field is investigated. Abstract: A kind of novel suspended nano thin films that exhibit excellent thermoacoustic effects is introduced as a promising candidate and a new approach for acoustic wave generation without mechanical vibration. Although several analytical models have been established in the past to determine thermoacoustic fields and to aid design optimization, there still show many limitations. In particular, those analyses in the past are mostly only available for one-dimensional problems. In this paper, a new numerical approach based on the boundary element method (BEM) is developed for predicting acoustic fields excited from a suspended thermoacoustic (TA) nano thin film with an arbitrary three-dimensional configuration. To substantiate the numerical model, experimental studies on the thermoacoustic emission of carbon nanotube (CNT) thin films are performed to verify the proposed method and excellent agreement is observed. By using the numerical approach, the accuracy and applicability of two recently developed analytical models for suspended CNT thin films are evaluated and discussed in detail. Furthermore, the influence of irregular deformation of CNT thin films on the acoustic field is investigated. Graphical abstract: Image, graphical abstract